1999
DOI: 10.1111/j.1745-9125.1999.tb00507.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender, Low Birth Weight, and Disadvantaged Environment in Predicting Early Onset of Offending: A Test of Moffitt's Interactional Hypothesis

Abstract: Little is known about the causes of an early onset of offending. In an attempt to shed light on this issue, some theoretical models have been advanced purporting to explain the reasons for an individual's early initiation into offending. In one of these models, Moffitt (1993) predicts that early onset of offending is caused by an interaction between (1) increased risk for neuropsychological disorders and (2) disadvantaged childhood environments. This study tests Moffitt's hypothesis concerning the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(121 citation statements)
references
References 80 publications
3
117
1
Order By: Relevance
“…Indeed, Moffi tt's propositions regarding the aetiology of adolescence-limited offenders and life-course persistent offenders have generated a substantial amount of empirical work, which has provided some evidence in favour of her theory (Moffi tt, 2006;Raine et al, 2005;Tibbetts and Piquero, 1999). Researchers have, however, been slow to test her account of delinquent abstention and much remains unknown about its causes and correlates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Moffi tt's propositions regarding the aetiology of adolescence-limited offenders and life-course persistent offenders have generated a substantial amount of empirical work, which has provided some evidence in favour of her theory (Moffi tt, 2006;Raine et al, 2005;Tibbetts and Piquero, 1999). Researchers have, however, been slow to test her account of delinquent abstention and much remains unknown about its causes and correlates.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, recent research has indicated that measures of neuropsychological deficits are predictive of antisocial behavioral patterns (Gibson et al, 2000;McGloin et al, 2006;Moffitt, 2006;Moffitt et al, 1996;Moffitt et al, 1994;Piquero, 2001;Raine et al, 2005;Tibbetts & Piquero, 1999;Turner et al, 2007). Some empirical research reveals measures of neuropsychological deficits have stronger effects on LCP offending when paired with a criminogenic environment.…”
Section: Moffitt's Developmental Taxonomymentioning
confidence: 99%
“…Several recent studies have examined the extent to which male-derived developmental models of antisocial and delinquent behaviour are applicable to girls (Tolan and Thomas, 1995;Kratzer and Hodgins 1999;Tibbetts and Piquero, 1999;Mazerolle et al, 2000;Cote et al, 2001;Fergusson and Horwood, 2002; Loeber and Farrington, 2001;Piquero and Chung, 2001;D'Unger et al, 2002;Hipwell et al, 2002;Broidy et al, 2003). Several of these efforts have identified an early-onset group of female offenders whose risk factors and life-course patterns are similar to boys, and who have worse outcomes as they age in comparison with late-onset girls.…”
Section: Gender Differences In Offending Trajectoriesmentioning
confidence: 99%